Analisis Pengaruh Tingkat Bagi Hasil, Inflasi Dan Tingkat PDB Terhadap Tabungan Mudharabah Di Bank Umum Syariah Periode 2014-2023 - Rana Ibtisamah; Noorsyah Adi Noer Ridha (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
Third-party funds (DPK) are an important indicator of banking performance. This study was motivated by the significant upward trend in DPK, reflecting the operational stability of Islamic banks. Several factors influencing third-party funds originate from within and outside of banking institutions. These factors include profit-sharing rates, inflation, and gross domestic product (GDP). Given the differing results from previous studies, the purpose of this study is to evaluate the influence of profit-sharing rates, inflation, and Indonesia's GDP on the amount of mudharabah savings at Islamic commercial banks (BUS). This study employs a quantitative approach with a descriptive method to gain a deeper understanding of the phenomenon and its implications. Data were obtained through documentation techniques from BUS annual reports from 2014 to 2023. The analysis used panel data regression with a sample of nine BUS in Indonesia. The analysis results show that the GDP variable positively and significantly affects Mudharabah savings, while the profit-sharing rate and inflation variables do not significantly affect these savings.